Functional Selectivity and Antinociceptive Effects of a Novel KOPr Agonist - Bedini, Andrea; Di Cesare Mannelli, Lorenzo; Micheli, Laura; Baiula, Monica; Vaca, Gabriela; De Marco, Rossella; Gentilucci, Luca; Ghelardini, Carla; Spampinato, Santi (Frontiers in Pharmacology, 2020)
Kappa opioid receptor (KOPr) agonists represent alternative analgesics for their low abuse potential, although relevant adverse effects have limited their clinical use. Functionally selective KOPr agonists may activate, in a pathway-specific manner, G protein-mediated signaling, that produces analgesia, over beta-arrestin 2-dependent induction of p38MAPK, which preferentially contributes to adverse effects. Thus, functionally selective KOPr agonists biased towards G protein-coupled intracellular signaling over beta-arrestin-2-mediated pathways may be considered promising therapeutics possibly devoid of many of the typical adverse effects elicited by classic KOPr agonists. Nonetheless, the potential utility of functionally selective agonists at opioid receptors is still highly debated; therefore, further studies are highly necessary to correlate the degree of signaling bias to particular pharmacological responses and to fully understand whether it will be possible to develop more effective and safer analgesics by exploiting functional selectivity at KOPr. In the present study we investigated in vitro functional selectivity and in vivo analgesic effects of LOR17, a novel KOPr selective agonist that we synthesized. LOR17-mediated effects on adenylyl cyclase inhibition, ERK1/2, p38MAPK phosphorylation and astrocyte cell proliferation were studied in HEK-293 cells expressing hKOPr, U87-MG glioblastoma cells and primary human astrocytes; biased agonism was investigated via cAMP ELISA and beta-arrestin 2 recruitment assays. Analgesia was assessed in mice via warm-water tail-withdrawal test, writhing assay and a model of oxaliplatin-induced neuropathic pain. Effects of LOR17 on locomotor activity, exploratory activity and mood were also assayed. We found that LOR17 is a selective, G protein biased KOPr agonist, inhibits adenylyl cyclase and activates early-phase ERK1/2 phosphorylation. Conversely to classic KOPr agonists as U50,488, LOR17 neither induces p38MAPK phosphorylation nor increases KOPr-dependent, p38MAPK-mediated cell proliferation in astrocytes. U50,488 and LOR17 display potent antinociception in models of nociceptive pain, whereas LOR17 but not U50,488 counteracts thermal hypersensitivity in oxaliplatin-induced neuropathy after single or repeated s.c. administration. Conversely, LOR17 does not cause any alteration of motor coordination, locomotor and exploratory activities or pro-depressant-like behavior. LOR17, therefore, emerges as a novel KOPr agonist displaying functional selectivity towards G protein signaling and analgesic effects in pain models, including oxaliplatin-induced neuropathy.